Detection method of tricresyl phosphate in water
By using an aluminum-based metal organic frame to detect the water body fluorescence, the problems of high TCP detection cost, long cycle and difficult pretreatment in the prior art are solved, and the TCP detection effect with high sensitivity and low detection limit is achieved.
Patent Information
- Application Number
- CN202211127029.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-16
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2042-09-16
AI Technical Summary
In the prior art, the detection of trithylyl phosphate (TCP) in water bodies has limitations such as high cost, long analysis cycle, and difficulty in pretreatment, and lacks a simple, sensitive and reliable detection method.
The water body to be tested was fluorescence detection by using aluminum-based metal organic frames (LMOFs), and an aluminum-based metal organic frame was prepared by hydrothermal reaction. Combined with the washing and vacuum drying process of ultrapure water, DMF and methanol, an aluminum-based metal organic frame powder suitable for TCP detection was obtained.
It realizes detection of high sensitivity and low detection limit for TCP, and has the advantages of wide linear range, strong anti-interference ability and simple operation, making it an effective method for detecting TCP.
Smart Images

Figure CN115656115B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of organophosphorus flame retardant detection, in particular to the technical field of tricresyl phosphate, and specifically to a method for detecting tricresyl phosphate in water. Background Art
[0002] Organophosphorus flame retardants (OPFRs) are additive plasticizers with good flame retardant properties. OPFRs are physically added to industrial finished products and released into the environment by leaching, abrasion and volatilization. Tricresyl phosphate (TCP) is a typical representative of aromatic OPFRs and is mainly added to hydraulic oil, engine oil and lubricating oil. Studies have shown that TCP has neurotoxicity, reproductive toxicity, hepatotoxicity and endocrine disruption. Ecological risk assessment shows that TCP has a high bioconcentration factor and poses a moderate risk to organisms. Therefore, the presence of TCP has irreversible harm to humans and the ecological environment. In addition, TCP has been detected in water sources such as drinking water, rivers and lakes, with concentrations ranging from ng / L to μg / L. Therefore, studying the detection method of TCP in the water environment is beneficial to the development of the environment. At present, the traditional detection methods of OPFRs are mainly gas chromatography-mass spectrometry, liquid chromatography-mass spectrometry and electrochemical methods, which have limitations such as high cost, long analysis cycle and difficult pretreatment process. Therefore, there is currently no simple, sensitive and reliable detection method for TCP. Summary of the invention
[0003] The main purpose of the present invention is to provide a method for detecting tricresyl phosphate in water, so as to solve the technical problem that tricresyl phosphate is difficult to detect in the prior art.
[0004] In order to achieve the above object, the present invention provides a method for detecting tricresyl phosphate in water, and the technical scheme is as follows:
[0005] The invention discloses a method for detecting tricresyl phosphate in water, which adopts a luminescent metal organic framework to perform fluorescence detection on the water to be detected; the luminescent metal organic framework is an aluminum-based metal organic framework.
[0006] As a further improvement of the present invention, the aluminum-based metal organic framework is obtained by hydrothermal reaction of an inorganic aluminum salt and 2-aminoterephthalic acid.
[0007] As a further improvement of the present invention, the molar ratio of aluminum ion to 2-aminoterephthalic acid is 1:(0.8-1.2); the hydrothermal temperature is 130-180° C., and the reaction time is 8-12 hours.
[0008] As a further improvement of the present invention, after the hydrothermal reaction, the precipitate is washed with ultrapure water, DMF and methanol in sequence, and then vacuum dried to obtain the aluminum-based metal organic framework powder.
[0009] As a further improvement of the present invention, the mass fractions of the elements in the aluminum-based metal organic framework are: O1s is 23.58%, N1s is 4.30%, C1s is 68.59%, and Al2p is 3.53%.
[0010] As a further improvement of the present invention, the single crystal size of the aluminum-based metal organic framework is less than 100 nm and the shape is gear-shaped.
[0011] As a further improvement of the present invention, the aluminum-based metal organic framework is firstly ultrasonically dispersed in ultrapure water and then added into the water body to be tested.
[0012] As a further improvement of the present invention, the incubation time of fluorescence detection is ≥30 min, the pH is 5-7, and the concentration of the aluminum-based metal organic framework is 100-150 mg / L.
[0013] As a further improvement of the present invention, the wavelength of the excitation light for fluorescence detection is 330 nm.
[0014] As a further improvement of the present invention, the linear relationship is y=0.0259+0.253x, R 2 =0.998, the detection limit is 0.054 μmol / L, wherein y=1-F / F0, F0 is the fluorescence intensity of the mixed solution of the aluminum-based metal-organic framework dispersion and the buffer solution, F is the fluorescence intensity of the mixed solution of the aluminum-based metal-organic framework dispersion, the water to be tested and the buffer solution, and x is the concentration of TCP in the mixed solution.
[0015] The present invention proposes for the first time to use luminescent metal organic frameworks (LMOFs) to detect TCP based on the following advantages of LMOFs: first, LMOFs have a regular microporous structure, exposed active sites and easily adjustable functional properties, and have been used to determine inorganic anions, metal cations and micromolecules; second, LMOFs also have excellent water stability and fluorescence properties, and are expected to perform fluorescence detection of TCP, thereby solving the limitations of existing detection methods such as high cost, long analysis cycle, and difficult pretreatment process.
[0016] The aluminum-based metal organic framework used in the present invention is a kind of LMOFs. It has been verified that the use of the aluminum-based metal organic framework for fluorescence detection of TCP has the advantages of low detection limit, high sensitivity, strong specific recognition ability, wide linear range, and strong anti-interference ability. It is expected to become a standard method for detecting TCP and has extremely strong practicality.
[0017] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments. Additional aspects and advantages of the present invention will be partially given in the following description, partially become apparent from the following description, or be learned through the practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] The drawings constituting a part of the present invention are used to assist in understanding the present invention. The contents provided in the drawings and their related descriptions in the present invention can be used to explain the present invention, but do not constitute improper limitations on the present invention. In the drawings:
[0019] Figure 1 Low-magnification and high-magnification SEM images of NH2-MIL-53(Al) powder.
[0020] Figure 2 This is the XRD pattern of NH2-MIL-53(Al) powder.
[0021] Figure 3 The infrared spectra of NH2-MIL-53(Al) powder, NH2-H2BDC and Al(NO)3·9H2O.
[0022] Figure 4 This is the full XPS spectrum of NH2-MIL-53(Al) powder.
[0023] Figure 5 This is the XPS fine energy spectrum of NH2-MIL-53(Al) powder at C1s, O1s, N1s and Al2p.
[0024] Figure 6 This is the thermogravimetric curve of NH2-MIL-53(Al) powder.
[0025] Figure 7 It is the fluorescence emission intensity of NH2-MIL-53(Al) at 435nm under the excitation light wavelength of 300-360nm.
[0026] Figure 8 This is the curve of the fluorescence intensity of NH2-MIL-53(Al) changing with time.
[0027] Fig. 9 Figure 2 is the fluorescence emission spectra of NH2-MIL-53(Al) dispersed in different solvents.
[0028] Fig.10 This is the curve showing the change of quenching efficiency with incubation time when NH2-MIL-53(Al) was used to test TCP.
[0029] Fig.11 This is the curve showing the change of quenching efficiency with buffer pH when NH2-MIL-53(Al) was used to test TCP.
[0030] Fig.12This is the curve showing the change of quenching efficiency with NH2-MIL-53(Al) concentration when NH2-MIL-53(Al) was used to test TCP.
[0031] Fig.13 Figure 3 is the fluorescence emission spectra of the mixed solution at different TCP concentrations, and the inset is the photograph of the mixed solution without and with TCP under 365nm ultraviolet light.
[0032] Fig.14 It is the linear fitting diagram of TCP concentration and quenching efficiency in mixed solution.
[0033] Fig.15 The quenching efficiency of NH2-MIL-53(Al) was tested for different organophosphorus pesticides and organophosphorus flame retardants.
[0034] Fig.16 The anti-interference ability test results of NH2-MIL-53(Al) when testing TCP.
[0035] Fig.17 These are the fluorescence lifetime decay curves of NH2-MIL-53(Al) and NH2-MIL-53(Al)+TCP.
[0036] Fig.18 UV-visible absorption spectra of mixed solutions at different TCP concentrations. DETAILED DESCRIPTION
[0037] The present invention is described clearly and completely below in conjunction with the accompanying drawings. A person skilled in the art will be able to implement the present invention based on these descriptions. Before describing the present invention in conjunction with the accompanying drawings, it should be particularly noted that:
[0038] The technical solutions and technical features provided in each part of the present invention, including the following description, may be combined with each other if there is no conflict.
[0039] In addition, the embodiments of the present invention involved in the following description are generally only a part of the embodiments of the present invention, rather than all the embodiments. Therefore, based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0040] About the terms and units in the present invention: The terms "include", "have" and any variations thereof in the description and claims of the present invention and related parts are intended to cover non-exclusive inclusions.
[0041] An embodiment of the method for detecting tricresyl phosphate in water of the present invention is to use an aluminum-based metal organic framework to perform fluorescence detection on the water to be detected; the aluminum-based metal organic framework is obtained by hydrothermal reaction of an inorganic aluminum salt and 2-aminoterephthalic acid (hereinafter represented by NH2-H2BDC), the molar ratio of aluminum ion to 2-aminoterephthalic acid is 1:(0.8-1.2), the hydrothermal temperature is 130-180°C, the reaction time is 8-12h, and after the hydrothermal reaction, ultrapure water, DMF and methanol are used to wash the precipitate in sequence, and then the aluminum-based metal organic framework (represented by NH2-MIL-53(Al)) is obtained by vacuum drying.
[0042] It has been verified that when the inorganic aluminum salt is Al(NO)3·9H2O, the molar ratio of aluminum ion and 2-aminoterephthalic acid is 1:1, the hydrothermal temperature is 150℃, and the reaction time is 10h, the obtained aluminum-based metal-organic framework has the best test effect when used for fluorescence test of TCP.
[0043] Figure 1 Low-magnification and high-magnification SEM images of NH2-MIL-53(Al) powder.
[0044] like Figure 1 As shown, NH2-MIL-53(Al) has a three-dimensional structure with a gear-like shape and a single crystal size of <100 nm, indicating that NH2-MIL-53(Al) has a large specific surface area and can provide more active sites, which helps to improve the detection effect of TCP.
[0045] Figure 2 This is the XRD pattern of NH2-MIL-53(Al) powder.
[0046] like Figure 2 As shown, the appearance of five diffraction peaks located at 8.7°, 10.4°, 15.0°, 17.5° and 26.4° proves the successful preparation of NH2-MIL-53(Al).
[0047] Figure 3 The infrared spectra of NH2-MIL-53(Al) powder, NH2-H2BDC and Al(NO)3·9H2O.
[0048] like Figure 3 As shown, the infrared spectrum of NH2-MIL-53(Al) is at 3505cm -1 and 3394cm -1 The unique peak at 2300-3300 cm-1 is consistent with the stretching vibration of the NH bond, indicating that -NH2 does not participate in the coordination. -1The broad band in the range originates from the hydroxyl group on the carboxyl group. The disappearance of this broad band in the infrared spectrum of NH2-MIL-53(Al) indicates that NH2-H2BDC is completely deprotonated in NH2-MIL-53(Al). 3+ The coupled carbonyl and free NH2-H2BDC are considered to be 1400-1700 cm -1 The corresponding vibration band in the range of 1012cm appears in the infrared spectrum of NH2-MIL-53(Al). -1 and 607cm -1 The two new peaks are mainly attributed to the stretching vibration of Al-O bonds.
[0049] Figure 4 This is the full XPS spectrum of NH2-MIL-53(Al) powder.
[0050] like Figure 4 As shown, at the binding energies of 532.08 eV, 399.08 eV, 285.08 eV, and 74.08 eV, NH2-MIL-53(Al) exhibits four characteristic peaks of O1s, N1s, C1s, and Al2p, with corresponding mass fractions of 23.58% for O1s, 4.30% for N1s, 68.59% for C1s, and 3.53% for Al2p, indicating that Al 3+ Successfully coordinated with NH2-H2BDC.
[0051] Figure 5 This is the XPS fine energy spectrum of NH2-MIL-53(Al) powder at C1s, O1s, N1s and Al2p.
[0052] like Figure 5 As shown, the two characteristic peaks at 284.68 eV and 288.28 eV in the C1s energy spectrum correspond to CC / C=C and CO, respectively; the two characteristic peaks at 531.48 eV and 532.48 eV in the O1s energy spectrum correspond to HO and Al-O, respectively; the two characteristic peaks at 398.68 eV and 399.08 eV in the N1s energy spectrum correspond to PhNH2 and PhN=C, respectively; the two characteristic peaks at 73.78 eV and 74.28 eV in the Al2p energy spectrum correspond to Al-O and Al-OH, respectively, proving that AlO4(OH)2 is produced in the NH2-MIL-53(Al) framework.
[0053] Figure 6 This is the thermogravimetric curve of NH2-MIL-53(Al) powder.
[0054] like Figure 6As shown, NH2-MIL-53(Al) begins to decompose at a high temperature close to 290°C, indicating that NH2-MIL-53(Al) has good thermal stability.
[0055] The following is a fluorescence test: before the test, NH2-MIL-53 (Al) powder was dispersed in ultrapure water and ultrasonically treated for 10 minutes; F0 is the fluorescence intensity of the mixed solution of NH2-MIL-53 (Al) dispersion and buffer (expressed as NH2-MIL-53 (Al)), and F is the fluorescence intensity of the mixed solution of NH2-MIL-53 (Al) dispersion, the water to be tested and the buffer (expressed as NH2-MIL-53 (Al) + TCP). The test of F0 is: 300 μL of NH2-MIL-53 (Al) dispersion is added to a quartz cuvette, and then the reaction solution is fixed to 1500 μL with HAc-NaAc buffer. The test of F is: 300 μL of NH2-MIL-53 (Al) dispersion and 150 μL of the water to be tested are added to a quartz cuvette in turn, and then the reaction solution is fixed to 1500 μL with HAc-NaAc buffer. After the mixed solution was incubated for a certain period of time, its fluorescence emission spectrum was measured on an FLS1000-stm steady-state / transient fluorescence spectrometer (Edinburgh, UK), with the excitation / emission slit widths both being 0.3 nm, thus obtaining the F0 and F of the mixed solution.
[0056] Unless otherwise specified: when the water body to be tested is an acetonitrile solution of TCP, the concentration of NH2-MIL-53(Al) in the mixed solution is 125 mg / L, the pH of the HAc-NaAc buffer solution is 6, and the concentration of TCP is 3.0 μmol / L; the excitation light wavelength of the fluorescence test is 330 nm.
[0057] Figure 7 It is the fluorescence emission intensity of NH2-MIL-53(Al) at 435nm under the excitation light wavelength of 300-360nm.
[0058] like Figure 7 As shown, NH2-MIL-53(Al) produced the strongest emission wavelength of 435nm under 330nm excitation.
[0059] Figure 8 This is the curve of the fluorescence intensity of NH2-MIL-53(Al) changing with time.
[0060] like Figure 8 As shown, the fluorescence intensity of NH2-MIL-53(Al) on the first, third, fifth and seventh days was basically the same, indicating that NH2-MIL-53(Al) had excellent fluorescence stability.
[0061] Fig. 9Figure 2 is the fluorescence emission spectra of NH2-MIL-53(Al) dispersed in different solvents.
[0062] like Fig. 9 As shown, NH2-MIL-53(Al) has the strongest fluorescence when dispersed in water.
[0063] Fig.10 This is the curve showing the change of quenching efficiency with incubation time when NH2-MIL-53(Al) was used to test TCP. Fig.11 This is the curve showing the change of quenching efficiency with buffer pH when NH2-MIL-53(Al) was used to test TCP. Fig.12 The curve of the quenching efficiency of NH2-MIL-53(Al) when testing TCP varies with the concentration of NH2-MIL-53(Al). The quenching efficiency is 1-F / F0.
[0064] like Figure 10-12 As shown, when the concentration of NH2-MIL-53(Al) in the mixed solution was 125 mg / L, the pH of the HAc-NaAc buffer solution was 6, and the incubation time was 30 min, TCP had the greatest quenching efficiency for NH2-MIL-53(Al).
[0065] Fig.13 Figure 3 is the fluorescence emission spectra of the mixed solution at different TCP concentrations, and the inset is the photograph of the mixed solution without and with TCP under 365nm ultraviolet light. Fig.14 It is the linear fitting diagram of TCP concentration and quenching efficiency in mixed solution.
[0066] like Fig.13 As shown in Figure 2, the fluorescence intensity of the mixed solution decreases with the increase of TCP concentration. Fig.14 As shown, the linear relationship is y = 0.0259 + 0.253x (R 2 =0.998, n=3), where y=1-F / F0, x is the concentration of TCP in the mixed solution, and the linear range is 0.3-3.0 μmol / L. The detection limit (LOD) is 0.054 μmol / L by the three-fold signal-to-noise ratio calculation formula. Therefore, in practical application, it is only necessary to test the F0 of NH2-MIL-53(Al) and the F of the mixed solution of NH2-MIL-53(Al) and the water to be tested, and then substitute them into the above equation to solve x to obtain the concentration of TCP in the mixed solution.
[0067] Fig.15 The quenching efficiency of NH2-MIL-53(Al) when testing different organophosphorus pesticides and organophosphorus flame retardants. All the test substances were dispersed in acetonitrile solution with a concentration of 3.0μmol / L.
[0068] like Fig.15 As shown, when detecting TCP, the quenching degree can reach 70%, while there is no obvious quenching effect when detecting other organophosphorus pesticides and organophosphorus flame retardants at the same concentration, indicating that NH2-MIL-53(Al) has a very beneficial selectivity for TCP.
[0069] Fig.16 The results of the anti-interference test of TCP by NH2-MIL-53(Al) are shown in Figure 2. + Mg 2+ , Ba 2+ , Mn 2+ Cr 3+ , Pb 2+ and NO3 - The concentration of K is 300 μmol / L. + 、Cr(VI)、Zn 2+ , Cu 2+ 、SO3 2- 、H2PO4 - The concentration of Ca is 30 μmol / L. 2+ 、Cd 2+ , Hg 2+ , Fe 3+ , Fe 2+ 、Co 2+ 、Al 3+ 、SO4 2- 、CO3 2- 、HPO4 2- 、F - , Cl - The concentration is 3μmol / L.
[0070] from Fig.16 It can be seen that NH2-MIL-53(Al) has strong anti-interference ability against TCP and can meet the needs of practical applications.
[0071] Fig.17 These are the fluorescence lifetime decay curves of NH2-MIL-53(Al) and NH2-MIL-53(Al)+TCP. Fig.18 UV-visible absorption spectra of mixed solutions at different TCP concentrations.
[0072] like Fig.17 As shown, the decay curves were fitted with double exponentials, and the fluorescence lifetimes of NH2-MIL-53(Al) before and after the addition of TCP were 15.18 ns and 15.25 ns, respectively. Fig.18 As shown in the figure, the absorbance of the mixed solution at 330 nm gradually decreases with the increase of TCP concentration. It can be seen that the quenching type is static quenching.
[0073] Using the Van'tHoff equation, the enthalpy change (ΔH) and entropy change (ΔS) during the test were calculated. Then, based on the determined ΔH and ΔS, the Gibbs free energy change (ΔG) was obtained from the Gibbs-Helmholtz equation. The calculated ΔG was negative, while ΔH and ΔS were positive, indicating that the possible mechanism of fluorescence quenching detection of TCP is that the water-insoluble TCP is wrapped around the hydrophobic pores of NH2-MIL-53(Al), forming a non-fluorescent complex through hydrophobic interactions, resulting in the static quenching of NH2-MIL-53-(Al).
[0074] In order to verify the practicality of the present invention, a spike test was carried out on actual environmental samples using the above linear relationship, as follows: tap water and lake water (particulate matter removed) were obtained, and a mixture of tap water or lake water and an acetonitrile solution of TCP was used as the water body to be tested. The test process was the same as above, and the test results are shown in Table 1.
[0075] Table 1
[0076]
[0077] In Table 1 , ND means not detected, NA means not acquired, and a means that the detected concentration was obtained as the mean ± standard deviation (SD) of three times.
[0078] As can be seen from Table 1, the recovery of spiked samples is 95.2-107.7%, and the relative standard deviation is less than 5.79%. Therefore, the test method of the present invention has good accuracy and reproducibility, and has great potential in the field of environmental analysis. Compared with electrochemical method and chromatography, it has the advantages of high sensitivity, strong anti-interference ability, simple operation, etc., and is an innovative method for detecting TCP.
[0079] In the above characterization and performance tests, the pH value of the solution was measured using a pHS-3C pH meter (Chengdu Century Ark Company, China), the XPS test was performed using a K-Alpha+ X-ray photoelectron spectrometer (Thermo Fisher Scientific, USA), the UV-visible absorption spectrum was tested using a USB-4000UV-vis spectrometer (Ocean Optics, USA), the FT-IR was performed using a PerkinLemmer Fourier transform infrared spectrometer, the XRD test was performed using an EMPYREAN X-ray diffractometer (PANalytical, the Netherlands), the SEM was performed using a JSM7800FPrime field emission scanning electron microscope (Japan Ltd.), and the thermogravimetric test was performed using a Swiss Mettler Toledo TGA / DSC3+ synchronous thermal analyzer.
[0080] The above is a description of the relevant contents of the present invention. A person skilled in the art will be able to implement the present invention based on these descriptions. Based on the above contents of the present invention, all other embodiments obtained by a person skilled in the art without creative work shall fall within the scope of protection of the present invention.
Claims
1. A method for detecting tricresyl phosphate in water, characterized in that: A luminescent metal organic framework is used to perform fluorescence detection on the water body to be tested; the luminescent metal organic framework is an aluminum-based metal organic framework; The aluminum-based metal organic framework is obtained by hydrothermal reaction of an inorganic aluminum salt and 2-aminoterephthalic acid; The molar ratio of aluminum ion to 2-aminoterephthalic acid is 1:(0.8-1.2); the hydrothermal temperature is 130-180°C, and the reaction time is 8-12h; After the hydrothermal reaction, the precipitate is washed with ultrapure water, DMF and methanol in sequence, and then vacuum dried to obtain aluminum-based metal organic framework powder; The mass fractions of the elements in the aluminum-based metal organic framework are: O1s is 23.58%, N1s is 4.30%, C1s is 68.59%, and Al2p is 3.53%.
2. The detection method according to claim 1, characterized in that: The single crystal size of the aluminum-based metal organic framework is less than 100 nm and the shape is gear-shaped.
3. The detection method according to claim 1, characterized in that: First, the aluminum-based metal-organic framework is ultrasonically dispersed in ultrapure water and then added to the water to be tested.
4. The detection method according to claim 1, characterized in that: The incubation time for fluorescence detection is ≥30 min, the pH is 5-7, and the concentration of the aluminum-based metal-organic framework is 100-150 mg / L.
5. The detection method according to claim 1, characterized in that: The excitation wavelength for fluorescence detection was 330 nm.
6. The detection method according to claim 1, characterized in that: The linear relationship is y = 0.0259 + 0.253x, R 2 =0.998, the detection limit is 0.054 μmol / L, wherein y=1-F / F0, F0 is the fluorescence intensity of the mixed solution of the aluminum-based metal-organic framework dispersion and the buffer solution, F is the fluorescence intensity of the mixed solution of the aluminum-based metal-organic framework dispersion, the water to be tested and the buffer solution, and x is the concentration of TCP in the mixed solution.